A imprescindível relação entre os centros municipais de educação infantil (CMEIS) e as famílias em Curitiba - Gomes, Alessandra de Fatima Borges (2010)
The objective of this dissertation is to analyze the relationship between the Municipal Centers of Nursery School (CMEIs) and the families in Curitiba, in the requirement participation. For such, it was studied the conception of childhood, child and family that is present in and orientates the public politics for the childhood. The research evidences that the treatment released the children and families, being safeguarded the different analyzed moments, is connected to the interest of a society of classes, ruled by the individualism, the consumerism and the exclusion. The relationship CMEI-family is discussed in Curitiba, from the end of the sixties to nowadays, period in that the Curitiba City Hall took the responsibility for the service to the small children and that the capital attracted intense migration flow, what intensified the social exclusion. It is standed out the performance of the social movements in the fight for the public services, as the day cares, in a tension context between the families and the provider, because of the disagreement between the presented vacancies and the demand. In the empiric pole, two CMEIs were researched under different glances: directors, educators, teachers and relatives. The conclusion was that for a lot of families the work of the centers is covered of a "favor" sense and that for most of the educators is not clear the paper of the CMEIs and of the families in the children's life. For so much, it is evoked that besides creating new public politics, it will be put in practice the politics already existent and engraved in laws, so that the population enjoys the nursery school as a right and not as a favor. The proposal subjects for the public politics and the administration of the education are also emphasized, such as: need of the formation courses for the nursery school teachers emphasize the importance of the work between the CMEIs and the families, in order to break with the common sense that put them in a closed microcosm; that the CMEIs can count with more professionals involved in the reality and the needs of the children and the families, enlarging the channels of the shared action principle; that the politics that guarantee the nursery school as a right of the child, such as the LDB and the ECA, are implemented and that new ones are built through a work including the people involved in the reality of the service units: directors, educators, teachers, intellectuals of the area, forums, social movements, civil association, universities and families; that the studies and the researches in the nursery school area can enjoy a communication channel no restricted to the academy.